THE EFFECT OF USING PHET IN THERMODYNAMIC PROCESS MATERIAL ABOUT CRITICAL THINKING SKILLS SENIOR HIGH SCHOOL STUDENT - Putri Anjani; Cecep E. Rustana; Lari Andres Sanjaya (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2023)
AbstractThermodynamic process material is a study of physics that is microscopic and not visible so that the learning process can use learning media in the form of PhET simulations. Critical thinking skills are one of the skills needed in the 21st century. The target of the study was a high school student with a sample of class XI MIPA MAN 1 Mojokerto. The purpose of this study was to determine the effect of the use of PhET on thermodynamic process materials on the critical thinking skills of high school students. The research method used is a quantitative method with an experimental approach with a pretest-posttest control group design. The result of this study was that there was a difference in the critical thinking skills of students in experimental classes and control classes with gain test scores in experimental classes of 0.73 (high category) and control classes by 0.36 (medium category). For the score of the effect size test with d-cohen's of 0.886. So the conclusion of this study is the effect of the use of PhET on thermodynamic process materials on the critical thinking skills of high school students with the level of effect on high categories.Keywords: PhET, Thermodynamic, critical thinking skills